Cross-cultural adaptation and validation of the universal Portuguese-version of the Pediatric Functional Assessment of Chronic Illness Therapy – Fatigue (pedsFACIT-F) - Karla P. Fernandes; Bruno S. Teixeira; Benjamin J. Arnold; Tânia M. da S. Mendonça; Sthela M. Oliveira; Carlos Henrique M. da Silva (Jornal de Pediatria, 2020)
Objective: To cross-culturally adapt and validate the universal Portuguese version of the Pediatric Functional Assessment of Chronic Illness Therapy – Fatigue (pedsFACIT-F). Method: The universal Portuguese version of the pedsFACIT-F was cross-culturally adapted and validated in 323 children and adolescents aged 8–18 years, 173 healthy individuals, and 150 with chronic diseases (cancer, juvenile idiopathic arthritis, and diabetes). Reliability (internal consistency and test–retest reliability) was assessed. Item response theory model assumptions were evaluated using confirmatory and exploratory factor analyses. Items were calibrated using a graded response model. Differential item functioning was assessed regarding age, gender, and clinical condition (healthy vs. chronic diseases). Results: No major cultural adaptations were needed. Internal consistency (Cronbach's alpha = 0.84) and test–retest reliability (intraclass correlation coefficient = 0.92) were good. CFA (CFI = 0.92, TLI = 0.90, RMSEA = 0.097) and CFE analysis confirmed sufficient unidimensionality. The data also fit the GRM and demonstrated good coverage of the fatigue construct (threshold parameters range: −1.42 to 4.56). No items demonstrated significant differential item functioning. Conclusion: The universal Portuguese version of the pedsFACIT-F provides a reliable, precise, and valid measure after being assessed by robust psychometric properties. Stability of the measurement properties of the pedsFACIT-F scale allows its use to assess fatigue in clinical research in Portuguese-speaking children and adolescents. Resumo: Objetivo: Adaptar transculturalmente e validar a versão portuguesa universal da escala Avaliação Funcional Pediátrica de Terapia de Doença Crônica – Fadiga (pedsFACIT-F). Método: A versão traduzida para o português universal e adaptada transculturalmente da escala pedsFACIT-F foi validada em 323 crianças (entre 8 e 18 anos), 173 saudáveis e 150 com doenças crônicas (câncer, artrite idiopática juvenil e diabetes). A confiabilidade foi avaliada pela consistência interna e confiabilidade teste-reteste. Os pressupostos do modelo da teoria da resposta ao item foram avaliados por meio da análise fatorial confirmatória e exploratória. Os itens foram calibrados segundo modelo de resposta gradual. O funcionamento diferencial do item foi examinado com respeito à idade, ao gênero e à condição de saúde (saudáveis versus doenças crônicas). Resultados: A adaptação cultural não apresentou dificuldades substantivas. A confiabilidade da consistência interna (alfa-Cronbach = 0,84) e do teste-reteste (correlação intraclasse = 0,92) foram adequadas. As análises da AFC (CFI = 0,92, TLI = 0,90, RMSEA = 0,097) e AFE confirmaram suficiente unidimensionalidade. O estudo de calibração demostrou bom ajuste do MRG e boa cobertura do construto fadiga (variação dos limiares das categorias de resposta: −1,42 a 4,56). Não foi verificada presença de funcionamento diferencial do item significante. Conclusão: A versão portuguesa universal da escala pedsFACIT-F é uma medida confiável, precisa e válida, verificada após análises de propriedades psicométricas robustas. A estabilidade das propriedades de medida da escala permite seu uso para avaliação de fadiga em estudos clínicos com crianças e adolescentes em países lusófonos.